Environmental niche variation and evolutionary diversification of the Brachypodium distachyon grass complex species in their native circum‐Mediterranean range. Issue 7 (1st July 2015) - López‐Alvarez, Diana; Manzaneda, Antonio J.; Rey, Pedro J.; Giraldo, Patricia; Benavente, Elena; Allainguillaume, Joël; Mur, Luis; Caicedo, Ana L.; Hazen, Samuel P.; Breiman, Adina; Ezrati, Smadar; Catalán, Pilar
Abstract : Premise of the study: We conducted environmental niche modeling (ENM) of the Brachypodium distachyon s.l. complex, a model group of two diploid annual grasses ( B. distachyon, B. stacei ) and their derived allotetraploid ( B. hybridum), native to the circum‐Mediterranean region. We (1) investigated the ENMs of the three species in their native range based on present and past climate data; (2) identified potential overlapping niches of the diploids and their hybrid across four Quaternary windows; (3) tested whether speciation was associated with niche divergence/conservatism in the complex species; and (4) tested for the potential of the polyploid outperforming the diploids in the native range. Methods: Geo‐referenced data, altitude, and 19 climatic variables were used to construct the ENMs. We used paleoclimate niche models to trace the potential existence of ancestral gene flow among the hybridizing species of the complex. Key results: Brachypodium distachyon grows in higher, cooler, and wetter places, B. stacei in lower, warmer, and drier places, and B. hybridum in places with intermediate climatic features. Brachypodium hybridum had the largest niche overlap with its parent niches, but a similar distribution range and niche breadth. Conclusions: Each species had a unique environmental niche though there were multiple niche overlapping areas for the diploids across time, suggesting the potential existence of several hybrid zones during the Pleistocene and the Holocene. No evidence of niche divergence was found, suggesting that species diversification was not driven by ecological speciation but by evolutionary history, though it could be associated to distinct environmental adaptations.